Psychological Impact of Parent-Adolescent Communication: A Critical Analysis - Shanthi Bavani V Raja Mohan (International Journal of Public Health Science (IJPHS), 2022)
The parent-adolescent relationship is an essential part of growing up and it is the key determinant of an adolescent’s growth. An adolescent is a stage of life which is unique as it is the phase for personality development. The nature of the relationship with their families during the adolescence stage determines their character.  The parental connection including the right kind of parenting style and inter-communication determine their growth. Previous studies have highlighted the relationship between parent-adolescents communication and the impact on adolescents’ psychological well-being.  However, the findings have not been conclusive.  In view of this, the current research aimed at assessing the level of parent-adolescent communication and the impact on adolescents’ self-esteem and the perceived stress inclusive of comparing differences between genders in Malaysia. The study was conducted using a quantitative research method through an online survey. The findings proved there is a significant relationship between parent-adolescent communication and the impact on self-esteem as well as stress levels among adolescents, where positive communication with parents, resulted in better self-esteem and lower levels of stress. Further, it was proven that female adolescents had lower self-esteem and higher stress compared to male adolescents. The study ends with a recommendation for further research.